Exemplifying the Bradford’s Law: an analysis of recent research (2014-2019) on capital structure - Alves, Francisco Ivander Amado Borges (Revista Ciências Sociais em Perspectiva, 2019)
The theme of capital structure is considered relevant within Corporate Finance, because it refers to decisions that influence the way firms finance, impacting the value and financial commitment of organizations. The main objective of this paper is to analyze the recent (2014-2019) world academic production on capital structure through the use of the Bradford Law. To do so, we collected the scientific articles available in the Web of Science. Data analysis was done through the description and use of the Bradford’s Law. The main findings indicated that the peak of scientific production on the subject occurred in 2017 (1,765 articles); it was identified that two authors stand out as those who participated in more articles in the theme. The application of the Bradford’s Law indicated that there is concentration of production in 5% of the journal (taken as 'core' of the publication on capital structure) which 2387 works. The journals considered 'important' correspond 19% (531 of them), publishing 2,262 articles. The other journals are considered 'noise', once they have published two or one articles. Because it is a relevant topic both in the business and academic aspects, as well as the fact that there are still gaps in the literature, new research is still expected, which makes it necessary to investigate how this research is behaving.